2017
DOI: 10.1002/bdra.23465
|View full text |Cite
|
Sign up to set email alerts
|

Both a frameshift and a missense mutation of the STRA6 gene observed in an infant with the Matthew‐Wood syndrome

Abstract: The diagnosis of Matthew-Wood syndrome should be considered in all fetuses with microphthalmia/anophthalmia. It requires an extensive ultrasound/MRI examination of the lung, heart, and diaphragm. Birth Defects Research 109:251-253, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The predicated minimal critical regions were labeled as the first critical region and second critical region and the main genes involved in both critical regions were listed. Low copy regions are presented as A (BP4), B (BP1), C and D (BP2), and E (BP3) [Color figure can be viewed at wileyonlinelibrary.com] pulmonary agenesis/hypoplasia, congenital cardiac defect, microphthalmia/anophthalmia, diaphragmatic hernias, and urogenital malformations (Sadowski et al, 2017); ARID3B has been reported as a candidate gene associated with congenital cardiac malformations (Uribe et al, 2014); CYP11A, a cholesterol side chain cleavage enzyme associated with congenital lipoid adrenal hyperplasia (Horikawa, 2004); MPI related to congenital disorder of glycation and hyperinsulinemic hypoglycemia (Deeb & Al Amoodi, 2018); EDC3 related to autosomal recessive intellectual disability (Ahmed et al, 2015), indicating the haploinsufficiency of these genes might contribute to the corresponding phenotypes of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The predicated minimal critical regions were labeled as the first critical region and second critical region and the main genes involved in both critical regions were listed. Low copy regions are presented as A (BP4), B (BP1), C and D (BP2), and E (BP3) [Color figure can be viewed at wileyonlinelibrary.com] pulmonary agenesis/hypoplasia, congenital cardiac defect, microphthalmia/anophthalmia, diaphragmatic hernias, and urogenital malformations (Sadowski et al, 2017); ARID3B has been reported as a candidate gene associated with congenital cardiac malformations (Uribe et al, 2014); CYP11A, a cholesterol side chain cleavage enzyme associated with congenital lipoid adrenal hyperplasia (Horikawa, 2004); MPI related to congenital disorder of glycation and hyperinsulinemic hypoglycemia (Deeb & Al Amoodi, 2018); EDC3 related to autosomal recessive intellectual disability (Ahmed et al, 2015), indicating the haploinsufficiency of these genes might contribute to the corresponding phenotypes of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation revealed no correlation with either the position or the type of mutation and demonstrated considerable intra-familial variability (Casey et al, 2011;Chassaing et al, 2009;Chitayat et al, 2007;Gerth-Kahlert et al, 2013;Golzio et al, 2007;Marcadier et al, 2016;Ng et al, 2013;Sadowski et al, 2017;Segel et al, 2009;West, Bove, & Slavotinek, 2009;White et al, 2008). The clinical manifestation revealed no correlation with either the position or the type of mutation and demonstrated considerable intra-familial variability (Casey et al, 2011;Chassaing et al, 2009;Chitayat et al, 2007;Gerth-Kahlert et al, 2013;Golzio et al, 2007;Marcadier et al, 2016;Ng et al, 2013;Sadowski et al, 2017;Segel et al, 2009;West, Bove, & Slavotinek, 2009;White et al, 2008).…”
Section: To the Editormentioning
confidence: 99%
“…During the last decade, a total of 44 patients with bi-allelic STRA6 mutations have been reported showing an extremely variable phenotype ranging from clinically isolated anophthalmia to complex presentations involving pulmonary, diaphragmatic, cardiac, renal, genital, and central nervous systems. The clinical manifestation revealed no correlation with either the position or the type of mutation and demonstrated considerable intra-familial variability (Casey et al, 2011;Chassaing et al, 2009;Chitayat et al, 2007;Gerth-Kahlert et al, 2013;Golzio et al, 2007;Marcadier et al, 2016;Ng et al, 2013;Sadowski et al, 2017;Segel et al, 2009;West, Bove, & Slavotinek, 2009;White et al, 2008). This complex phenotype was referred to by many different names including MWS, PDAC syndrome, PMD (pulmonary agenesis-microphthalmia-diaphragmatic) defect, Spear syndrome, and Syndromic Microphthalmia 9 (MCOPS9, OMIM 601186).…”
mentioning
confidence: 99%